Telepresence as a Mediator from Characteristics of FB Posts to the Integration of Social Media Based Brand Community - Srivardhana, Thongchai (Dusit Thani College Journal, 2020)
This research paper proposes and proves the research framework containing Facebook (FB) Page posts, Telepresence, and Integration of Social Media Based Brand Community. The population in this study are followers of a professional football club’s FB who have engaged with the FB posts for at least a month. All fit indices fall in acceptable ranges with all significant inferential statistics. This research contributes to our knowledge that FB page Posts containing two important characteristics—vividness and interactivity influence not only the posts’ popularity but also toward the integration of social media based brand community and through telepresence.